A comparative assessment of a multi-generational workforce on their work performance as employees of Manila Jockey Club, Inc. - Genrei S. Bismanos, Jham Kristine A. Marcaida, Kendrick Clement M. Reyes, Allyka B. Siguen, Hazel Anne R. Vicencio 4 0 16; 5
Introduction The number of workers in organizations nowadays is constantly increasing with multiple generations. The Philippine Statistics Authority (2018) reports that more than 60% of people fifteen years old and older are already employed. On the one hand, the age group of 25 to 34 years represented 27.1% of all employed people, making up most of the workforce. However, the age group of 35 to 44 made up the second-largest group, with 23.1%, followed by the age group of 45 to 54 years old and above, with 18.4%. As a result of this tendency, it is now more common than ever for different generations to work together in the same workplace We are working with five generations for the first time in contemporary times. The generational diversity prevalent in most firms can offer a variety of issues, from Traditionalists born before 1945 to Gen Z. A lot has been said about this subject, mainly about how to interact with the various generations at work. Some people believe that this kind of diversity prevents growth. Employees from different generations can and should be a unique business advantage today. The diversity of opinions and expertise from a large group of people can benefit the business and enable employees to perform at the highest level (Gay, 2017). A varied team in terms of age and experience can benefit any company by bringing a wealth of skills and viewpoints. However, in today's scattered, remote work contexts, generational differences can also cause friction at work and present problems to their work performance management. This chapter will elaborately present the study with its background, statement of the problem, the significance of the study, hypothesis, and scope and limitations.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2